2021
DOI: 10.1364/oe.440115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstrations of DSP-enabled flexibility, adaptability and elasticity of multi-channel >72Gb/s over 25 km IMDD transmission systems

Abstract: DSP-enabled multi-channel aggregation techniques are promising for cost-effectively improving the flexibility, adaptability and elasticity of fronthaul transport networks. By utilizing orthogonal digital filtering in multi-channel aggregation in IMDD transmission systems, two DSP-enabled matching filter (MF)-free multi-channel aggregation techniques respectively based on SSB OFDM and orthogonal DSB OFDM have been reported; however, the SSB (DSB) technique has a drawback of relatively high digital filter DSP co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It is also interesting to point out that when the last IFFT operation size is fixed, the optimal clipping ratio is independent of channel count, as verified in Figure 8 . As seen in Figure 10 , with the identified optimal clipping ratio, when the channel count increases, the maximum aggregated transmission capacity is slightly reduced because of clipping-induced channel interferences [ 1 ], and it can also be found that every additional two-channel increase in the channel count can only lead to <1.2 Gb/s reductions in the aggregated capacity when the channel count is >4. As illustrated in Figure 9 , when the size of the last IFFT operations is fixed, clipping ratio has a linear relationship with CSPR, which is independent of channel count.…”
Section: Transmission Performancesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also interesting to point out that when the last IFFT operation size is fixed, the optimal clipping ratio is independent of channel count, as verified in Figure 8 . As seen in Figure 10 , with the identified optimal clipping ratio, when the channel count increases, the maximum aggregated transmission capacity is slightly reduced because of clipping-induced channel interferences [ 1 ], and it can also be found that every additional two-channel increase in the channel count can only lead to <1.2 Gb/s reductions in the aggregated capacity when the channel count is >4. As illustrated in Figure 9 , when the size of the last IFFT operations is fixed, clipping ratio has a linear relationship with CSPR, which is independent of channel count.…”
Section: Transmission Performancesmentioning
confidence: 99%
“…It can be seen from Figure 5 and Figure 6 that clipping can effectively reduce PAPRs by introducing signal distortions [ 18 ]. Such signal distortions can result in unwanted channel interferences [ 1 , 11 ], which can be further mitigated by adopting clipping noise cancellation techniques [ 19 ].…”
Section: Transmission Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional IMDD transceivers can only operate at predefined speeds and provide static and fixed-grid connections [3]. They thus cannot cost-effectively meet the stringent requirements of the next generation of optical access networks and mobile access networks in terms of flexibility, elasticity, scalability, and upgradability [4][5][6].…”
Section: Introductionmentioning
confidence: 99%